PENERAPAN ALGORITMA C4.5 DALAM KLASIFIKASI RELEVANSI JENIS PEKERJAAN PADA ALUMNI STMIK DHARMA WACANA KOTA METRO - Anwar, Edi; Sutomo, Budi (Jurnal informasi dan komputer, 2023)
One of the things that becomes a benchmark for a tertiary institution in terms of the quality of education is the level of success in producing alumni who can work after graduating from the tertiary institution. However, many university alumni who have been equipped with knowledge that is in accordance with the needs of the industry with the relevance of their education, but get jobs that are not in accordance with the relevance of their education. This study aims to implement the classification method with the C4.5 algorithm in the classification of the relevance of types of work on the alumni data of STMIK Dharma Wacana Metro City and to find out the factors that influence the level of job relevance according to their education. In this study the method used is classification with the C4.5 algorithm, with the final result in the form of a decision tree that will be used to analyze the factors that influence the relevance of the type of work to alumni of STMIK Dharma Wacana Metro City. In the research, the data used were alumni data from STMIK Dharma Wacana Metro City obtained from distributing questionnaires. The results of the implementation based on the decision tree that formed the attributes that most influenced the relevance of the type of work of alumni of STMIK Dharma Wacana Metro City Expertise based on fields of knowledge (IT/SI). This is because the attribute Expertise based on the field of science (IT/SI) as the root of the decision tree has the highest gain ratio value among the other attributes, followed by other influential attributes, namely GPA, Knowledge in the field or discipline (IT/ SI), Gender, Emphasis on learning in the field of science (IT/SI) during lectures, Facilities and infrastructure in pursuing the field of science during lectures (IT/SI) and the last attribute that has an effect is the year of graduation.